EXTENSION OF LINEAR n-FUNCTIONALS DOMINATED BY SEMI-n-NORM - Srivastava, Neeraj; Bhattacharya, S.; Lal, S. N. (Matematichki Bilten, 2005)
In this paper we establish an extension theorem for a complex linear \(n\)-functional dominated by a semi-\(n\)-norm.